ELEMENTS OF FICTION IN ENGLISH MOVIE - Pipit Rahayu (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This Paper discusses about the analysis of Elements of Fiction in English movie. In this case, focuses on Plot and setting. Plot is the way in which a story's events are arranged, while setting is where the story takes place somer where and at some time. The English movie used in this paper was "Twilight". Twilight is a 2008 American vampire romance film based on Stephanie Meyer. Directed by Catherine Hardwicke, this movie stars are Kristen Stervaft and Robert Pattinson. It is the first film in The Twilight Saga film series. This film focuses on the development of the relationship between Bella Swan (a teenage girl) and Edward Cullen (vampire), and the subsequent efforts of Cullen and his family to keep Swan safe from a coven of evil vampires. The technique of data analysis is descriptive qualitative. The steps involved analyzing the component of plot and setting. It was indicated from exposition, rising action, climax, falling action, resolution and historical setting, geographical setting and physical setting. In collecting the data, the test and participant observation was used. The Sample in this paper was the third semester rvhich consists of 34 students. Based on the analysis. it can be concluded that 18 students (52,9%) vere good category in identifuing plot in twilight movie and (73,52%) u'ere also in good category in identifuing setting in twilight movie. In addition, watching English movie is one of the interesting and motivated media for students in learning introduction to literature, especially in analyzing elements of fiction.